(untitled) (Quest Journal of Management and Social Sciences, 2026)
Background: Electric vehicle (EV) adoption is accelerating globally due to environmental and economic concerns. Understanding consumer purchase intention in emerging markets, such as Kathmandu Valley, is crucial for effective market development. However, adoption remains low locally, partly due to infrastructure and behavioral barriers. Purpose: The study aims to investigate the factors influencing consumers’ purchase intention for electric cars in Kathmandu Valley, Nepal, with a focus on psychological, social, and control-related determinants. Design/methodology/approach: An explanatory research design based on an extended Theory of Planned Behavior (TPB) framework was employed. Data were collected from 403 residents through structured questionnaires using online and offline convenience sampling. Structural Equation Modelling (SEM) with Partial Least Squares (PLS) was applied to test the relationships between Attitude, Emotion, Subjective Norm, Perceived Behavioral Control, and Purchase Intention. Findings: Emotion, Subjective Norms, and Perceived Behavioral Control were found to have a significant positive effect on EV purchase intention, indicating that decisions are shaped by feelings, social pressures, and practical considerations of resources and infrastructure. Attitude, however, was not a significant predictor, suggesting that general positivity toward EVs alone does not translate into purchase intention. The main adoption barriers identified were insufficient charging infrastructure and technical/display issues, while key solutions included expanding charging stations, improving access to spare parts, and implementing supportive fiscal policies such as tax reductions and subsidies. Conclusion EV adoption in Kathmandu Valley shows strong potential but is constrained by infrastructure and social-psychological factors. Successful promotion of electric mobility requires more than economic incentives, it depends on fostering positive emotional connections, leveraging social networks for influence, and establishing reliable, well-equipped support infrastructure to enhance consumers’ perceived control and confidence in ownership. Addressing these factors can accelerate adoption and make EVs a viable and attractive alternative in the region. Keywords: Electric Vehicles, Purchase Intention, Theory of Planned Behavior, Consumer Behavior, Adoption Barriers, Emerging Market